Pengaruh Gaya Mengajar Resiprocal Style terhadap Keterampilan Servis Atas Bola Voli Siswa SMP - Novia Novia; Indria Susilawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effect of the reciprocal teaching style on students’ overhand service skills in volleyball at the junior high school level. A pre-eksperimental method with a one-group pretest-posttest design was employed. The participants consisted of 42 seventh-grade students enrolled in physical education classes. The instrumens used was an overhand service skill test. Data were analyzed using descriptive statistics, normality testing, and hypothesis testing with the Wilcoxon Signed Rank Test. The findings revealed that students’ overhand service skills prior to the implementation of the reciprocal teaching style were at a moderate level, with a mean score of 65.21, which increased to 71.69 after treatment. Furthermore, the Wilcoxon test yielded a significance value of 0.000 (<0.05), indicating a statistically significant effect of the reciprocal teaching style on improving students’ overhand service skills. Therefore, the reciprocal teaching style is effective in volleyball instruction, particularly in enhancing basic technical skills through cooperative interaction and peer feedback. Keywords: Volleyball, Reciprocal teaching Style, Top Serve